Altered O-Glycans in stimulated whole saliva from patients with primary Sjögren’s syndrome and non-pSS sicca - Sarah Kamounah; Kristina A. Thomsson; Christiane Elisabeth Sørensen; Eric Paul Bennett; Niclas G. Karlsson; Anne Marie Lynge Pedersen (Scientific Reports)
Abstract To investigate if salivary O-linked glycans are altered in primary Sjögren’s syndrome (pSS), and thus contributing to explain symptoms of oral dryness, and an impaired oral mucosal barrier function leading to changes in microbial metabolism and colonization by both pathogenic and commensal microorganisms and increased prevalence of oral diseases. O-linked oligosaccharides from stimulated whole saliva (SWS) samples from 24 patients with pSS, 38 patients with non-pSS sicca, and 23 healthy controls were analyzed using liquid chromatography mass spectrometer (LC-MS). Non-fractionated reduced and alkylated saliva was dot-blotted to PVDF-membrane and O-linked oligosaccharides were released using reductive beta-elimination. The 50 most abundant glycans were identified and their intensity compared for each sample, reflecting the relative abundance of individual monosaccharide residues. Comparison of the compositions of O-glycans in SWS samples revealed higher relative levels of sialic acid (NeuAc) and lower levels of neutral amino-monosaccharides (HexNAc) in pSS and non-pSS sicca patients than in the healthy controls. MS2 fragmentation analysis of salivary O-glycans suggests that altered sulfation, fucosylation, sialylation and distribution of core types may all contribute to the observed alteration, directly or indirectly. Additionally, the short disaccharide sialyl-Tn was most abundant in the saliva samples from patients with pSS. Our findings indicate that the salivary mucin-type O-glycan profile is altered in pSS, reflecting a dysfunction of the post-translational modification of salivary mucins leading to rheological changes of saliva, oral dryness symptoms, and impaired oral mucosal barrier function. The pathophysiological significance of the aberrant O-glycosylation needs further elucidation.